A case of severe odontogenic infection in Kikuchi‐Fujimoto disease. (23rd October 2021) - Platais, Christopher; Henien, Marianne; Patel, Vinod
Abstract: Kikuchi‐Fujimoto disease (KFD) is a rare cause of cervical lymphadenopathy and is not well understood. We report a case of deep neck space infection arising from a small dentigerous cyst associated with an impacted mandibular third molar in a patient with a recent diagnosis of KFD. We consider the unusual severity of the clinical presentation and suggest that KFD may have a role in the exaggerated response to a minimal dentigerous cyst.